Digital Philanthropy and Community Empowerment Model: An Analysis of the Role of the Sedekah Rombongan Movement in Indonesia - Hendrawati, Titi (Unram Journal of Community Service, 2025)
The philanthropic movement in Indonesia has undergone significant changes with the emergence of organisations such as Sedekah Rombongan (SR), which utilises digital technology and religious values in its operations. SR was born from grassroots initiatives and developed into an organisation with significant impact. This study aims to analyse the role of SR in empowering marginalised communities, with a focus on the operational model that integrates survey, benefit, and assistance. A descriptive qualitative method was used to explore the experiences and views of volunteers and beneficiaries. Data was collected through direct interviews with SR administrators and beneficiaries who have participated in the program for more than three months. The research also observed how SR uses social media to raise funds and build awareness about philanthropy. The results show that the SR model not only provides material assistance but also mentors beneficiaries on an ongoing basis. A rigorous survey process ensures aid is channelled to those truly in need, while transparency and accountability build trust between donors and beneficiaries. In addition, mentoring has a significant positive impact on beneficiaries, creating sustainable social change. Despite its many successes, SR faces challenges in terms of resource management and limited access in remote areas. This research identified the need to improve monitoring and evaluation systems and strengthen training for volunteers to ensure quality service delivery. SR needs to continue innovating in the management and distribution of aid to maintain the program's sustainability. Based on the results obtained, it is recommended that SR increase collaboration with the government and other organisations to expand the program's reach and strengthen policy advocacy. This will result in greater impact in community empowerment. The utilisation of blockchain technology and artificial intelligence (AI) can also improve the efficiency and transparency of SR operations. With a collaborative approach involving all stakeholders, SR can continue to function as an adaptive and sustainable philanthropy model. This research is expected to contribute to a deeper understanding of the practice of community-based philanthropy in Indonesia. SR can be a role model for other philanthropic organisations.